Should unthinned oak stands of advanced age (≥ 60 yr) be thinned?. (18th May 2016) - Demchik, Michael C.; Conrad, Joseph; Vokoun, Melinda
ABSTRACT: Oaks ( Quercus sp.) account for nearly one-third of the sawtimber harvest in Wisconsin. As trees age, their ability to respond to thinning is reduced; therefore, the objective of this study was to determine whether thinning previously unthinned oak stands of advanced age (≥ 60 yr) would achieve biological, financial, and operational objectives. During 2014, we conducted an inventory of 25 oak stands in northern Wisconsin. Fifteen received their first thinning 8–14 yr ago at ages 60–78 yr and 10 had never been thinned. Stand-level volume growth, logging costs, and net present values were estimated for each site. The age and site index of the thinned and unthinned sites were not significantly different ( p > .10). Thinned and unthinned sites grew comparable net volumes per ha (5.09 and 5.90 m 3, respectively); however, because this growth was concentrated on fewer trees, the trees on the thinned sites responded vigorously to thinning. As age at first thinning increased, growth response was reduced ( p = .067); however, thinning still increased the growth of residual trees. Thinned sites had higher net present values compared to unthinned sites ( p < .01) and logging costs were 10.6% lower ( p = 0.06). Overall, for stands between 60 and 78 years old, thinning was beneficial financially, operationally, and biologically.